PTU-004 The use of a "Moodle" Virtual Learning Environment (VLE) in Gastroenterology Training. (4th June 2013) - Rogers, D; Delahooke, T
Abstract : Introduction: The East Midlands Healthcare Workforce Deanery launched a VLE pilot in 2009 and subsequently rolled out the "Moodle" based platform to all Postgraduate schools. Some schools have used the VLE as an information repository only, but The School of Gastroenterology South was keen to exploit the full potential by developing interactive activities and evaluating their acceptability to trainees. Methods: In addition to using our "Moodle" page as a repository for training information, rotation and teaching event details and Journal club records we have also developed Endoscopy and Gastro-radiology atlases. Forums for Case, Endoscopy and Radiology Presentations have also been developed, and these are "Question and Answer" forums in which trainees post a short introduction and others reply with their thoughts. Other trainee's postings become visible once an individual has posted themselves, thus removing the chance that all replies will mirror that of the first reply. As the discussion progresses the case is updated by the original poster to mirror how the case developed in real life. To augment the learning during regional teaching, quizzes are placed on the VLE following each session and immediate feedback is given. Teaching evaluation is also obtained through the VLE which simplifies the analysis of this feedback. We have surveyed how the trainee's use the VLE and which areas they find most useful via a questionnaire in order to guide further development. Results: Pleasingly all trainees were aware of the existence of a VLE for Gastroenterology and have accessed it at some stage. The case discussion forums are used most and found useful by all trainees. All those who have used the Endoscopy and Radiology libraries find them useful, and all trainees report finding the Journal Club records and the single point of access for training information, e-learning resources and rotation details useful. The quizzes following teaching sessions were seen as less helpful, but two thirds still found them to be useful. The medical apps area is not used by any trainees and this may relate more to the ready access to medical apps available on smart phones. Conclusion: The interactive use of the VLE has been accepted by most trainees and has led to evidence based discussion around cases and consolidation of learning together with providing a repository for the storage of information and resources. The "moodle" platform requires only simple IT skills and material can be developed by anybody with basic word processor skills. Further development is planned that will include blueprinting of the curriculum to the rotation and learning material available, together with further interactive case discussions. Disclosure of Interest: None Declared